2014
DOI: 10.1117/1.jnp.8.083093
|View full text |Cite
|
Sign up to set email alerts
|

Three- and two-photon upconversion luminescence switching in Tm3+/Yb3+-codoped sodium niobate nanophosphor

Abstract: Intense infrared-to-visible upconversion (UC) emission in Tm 3þ ∕Yb 3þ -codoped sodium niobate (NaNbO 3 ) nanocrystals under resonant excitation at 976 nm is presented. The results showed that by increasing the pump power/intensity, a strong reduction is observed at the 800∕480 nm emitted intensity ratio, characterizing what can be denominated as laser pump power-induced color tunability or luminescent switching. The physical origin is discussed with a focus on tailoring of luminescent switchers to operate at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The 3 F 4 state is then excited to the 3 F 2,3 state through excited state absorption (ESA), which then either decays to the 3 H 6 ground state with the emission of red light at 677 nm or relaxes to the 3 H 4 state through a phonon-assisted nonradiative transition process. The 3 H 4 state either decays back to the 3 H 6 ground state with the emission of near-infrared light at 780 nm or is excited to the 1 G 4 state through a second ESA process, after which the 1 G 4 state decays to the 3 H 6 ground state with the emission of blue light at 486 nm, or decays to the 3 F 4 state with the emission of red light at 660 nm. , The intensities of ultraviolet emission peaks at 308/359/376 nm are dependent on the populations of the Tm 3+ : 1 D 2 and the 1 I 6 states. For the population of the 1 D 2 energy state, the energy difference between the Tm 3+ : 1 G 4 and 1 D 2 state calculated from the absorption spectra is 6.46 × 10 3 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The 3 F 4 state is then excited to the 3 F 2,3 state through excited state absorption (ESA), which then either decays to the 3 H 6 ground state with the emission of red light at 677 nm or relaxes to the 3 H 4 state through a phonon-assisted nonradiative transition process. The 3 H 4 state either decays back to the 3 H 6 ground state with the emission of near-infrared light at 780 nm or is excited to the 1 G 4 state through a second ESA process, after which the 1 G 4 state decays to the 3 H 6 ground state with the emission of blue light at 486 nm, or decays to the 3 F 4 state with the emission of red light at 660 nm. , The intensities of ultraviolet emission peaks at 308/359/376 nm are dependent on the populations of the Tm 3+ : 1 D 2 and the 1 I 6 states. For the population of the 1 D 2 energy state, the energy difference between the Tm 3+ : 1 G 4 and 1 D 2 state calculated from the absorption spectra is 6.46 × 10 3 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Other investigations on the luminescence properties of lanthanide-based systems with NPs, nanorods or systems assembled using sol-gel techniques have been reported in the literature [17,22,27,33,34,38,40,43,45,49,50,60,61,67,73,78,82,88,93,107,[127][128][129]133,136,140,142,143,149,163,[169][170][171]176,178,201,211,212,214,[235][236][237][238][239][240][241][242][243][244][245]…”
Section: Nanoparticles Nanorods and Sol-gel Processmentioning
confidence: 99%
“…In recent decades, the interest of scientists in phosphor materials with sizes ranging from nanometers to micrometers has been increasing due to their abundant applications in fields such as lighting, color displays, medicine, solid laser, light emitting diodes, luminescence switching, and solar cells. [1][2][3][4][5][6][7][8] The luminescence of these materials is usually based on the emission of trivalent rare earth (RE 3+ ) ions in the vis or IR regions under excitation of VUV, UV, or vis irradiations. It is reported that fluoride NCs based on MLnF 4 (M = Li, K, Na, and Ln = La-Lu) compounds are the ideal host matrices for the luminescence of RE 3+ ions due to their low phonon energy.…”
Section: Introductionmentioning
confidence: 99%